Ocular manifestations in patients with hematologic malignancies (Ukrainian Journal of Ophthalmology, 2025)
Ocular manifestations in patients with hematologic malignancies may develop either as a primary sign of the underlying disease or as relapse in remission. In addition, ocular involvement may result from anemia, thrombocytopenia, and coagulopathy, as well as infectious lesions caused by complications developing in the patient. Moreover, ocular toxicity may develop if the patient is treated with cytostatic and/or targeted agents. The review indicates that leukemia should be ruled out in the presence of ocular lesions (especially, hemorrhagic complications and retinal and optic nerve lesions). In addition, while examining a patient in remission after therapy for hematologic malignancy, recurrent hematologic malignancy should be ruled out in the presence of ocular manifestations. Moreover, a high index of suspicion for ocular toxicity should be maintained while examining a patient treated with either conventional cytostatics or target therapy, because any ocular lesions in this patient may be manifestations of ocular toxicity, and if so, the patient requires urgent intervention or discontinuation of the therapy for underlying disease.
Keywords: leukemia; hematologic malignancies; ocular manifestations; hemorrhages; retinopathy; optic nerve